(untitled) (Research, Society and Development, 2024)
There is increasing research on the influence of spirituality on the lives of patients undergoing cancer treatment. Spirituality is an important dimension of human life, aiding patients in their search for the sacred, helping them face their prognosis, and improving their quality of life. This study aims to identify the real influences of strengthening and spiritual support for adult patients diagnosed with cancer and undergoing cancer treatments, as reported in the literature. By fully recognizing these influences, we can provide progressively more individualized care and assistance to these individuals. This is a systematic literature review on the influence of spirituality in adult patients undergoing cancer treatments. The review includes articles from the LILACS, MEDLINE, and PubMed databases in Portuguese and English, published between 2016 and 2021. Thirteen relevant studies were selected for this review. Most of these articles discussed the correlation between spirituality and the acceptance of prognosis and quality of life, with only one study diverging from these findings. The influence of spirituality in the biopsychosocial process of patients diagnosed with cancer is evident, contributing to their fight against the disease. Understanding this topic is particularly important for healthcare professionals, especially the nursing team, who provide direct and continuous care to patients.